SOME PROBLEMS OF LINEAR PROGRAMMING WITH A LARGE NUMBER OF VARIABLES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This scientific work considers some types of problems related to determining optimal plans for the aggregate material production of individual industries and enterprises using linear programming.